Effectiveness of Injectable Iron in the Management of Severe Iron Deficiency in Children in Ouagadougou - Ouattara, Roselyne; Yonaba, Caroline; Zoungrana, Chantale; Zan, Angèle; Ouedraogo, Flore; Koueta, Fla (International Journal of Child Health and Nutrition, 2022)
Background: Iron deficiency anemia affects 90% of children in Burkina Faso. These studies on the effectiveness of injectable iron are rare in low-income countries with high infant and child mortality related to anemia. Methods: This has been an observational study to assess the effectiveness of injectable iron in children under five years old admitted to the pediatric ward of the Yalgado Ouédraogo University Teaching Hospital (YO-UTH), in 2019, in Ouagadougou, Burkina Faso. Findings: Thirty-five (35) children with severe iron deficiency anemia (average age 2.5 years), 60 %( n=21) of whom had decompensated anemia and required transfusion, were treated with injectable iron polymaltose hydroxide and followed up for one month. On average, 226.9± 45.5mg of iron were injected over an average treatment duration of three days. The mean hemoglobin count increased from 4.7± 0.95g/dl at baseline to 9.7±1g/dl (an increase of 4.9g/dl) one month later (p<0.001). The mean corpuscular volume increased from 66.7±4.7fl to 81.5±3.7fl (p<0.001), and that of the ferritinemia varied from 0.02±0.005μg/ml to 0.83±0.09μg/ml (an increase of 0.81μg/ml, p<0.001) and the mean sideremia increased from 4.8±2.1μmol/l to 40.4±5.5μmol/l. No side effects were noted. Conclusion: By avoiding transfusion in most patients, the use of injectable iron in proven and severe iron deficiency anemias could be a solution in case of blood deficit.